Estimating the Effect of Working from Home on Parents' Division of Childcare and Housework: A New Panel IV Approach - Simone Schüller (CESifo GmbH, 2025)
This study investigates whether (and how) working from home (WFH) affects the gender division of parental unpaid labor. I use the recent COVID-19 pandemic that brought an unanticipated yet lasting shift to WFH combined with a measure of occupational WFH feasibility (Alipour et al. 2023) as a quasi-experiment to employ an instrumental variable (IV) approach and estimate causal effects. I use unique longitudinal data from the "Growing up in Germany" (AID:A) panel study, which administered a pre-pandemic wave in 2019, and a post-pandemic wave in 2023. AID:A contains rich information on mothers' and fathers' time use for work, commuting, childcare, and housework. I find that the most robust effects emerge for paternal WFH intensity (at least weekly WFH) on parental division of housework: families in which fathers start weekly WFH in the period 2019 to 2023—due to their occupational WFH capacity in combination with the pandemic WFH-boost—experience a significant decrease in the maternal share of parental housework. Interestingly, this shift appears to be mainly driven by a reduction of maternal time use for housework (combined with an increase of her work hours) and less by an increase in paternal time use for housework suggesting cross-parent effects of WFH.
Keywords: D13; I31; J13; 330; working from home; childcare; housework; time use; gender equality; Covid-19; AID:A panel survey